Myopa nebulosa sp. nov. and Myopa bozinovici sp. nov. (Diptera: Conopidae): New thick-headed flies from a threatened biodiversity hotspot in central Chile - Barahona-Segovia, Rodrigo M.; Barceló, Matías (Zootaxa, 2020)
Diptera is one of the most speciose groups within Insecta, but there are deep gaps in knowledge of the South American faunas. Conopidae, also known as thick-headed flies, inhabit many habitats around the world, and are particularly diverse in the Neotropical region. Despite this, southern South American species of this group are poorly known and many genera are under-represented in museum collections. Only four Neotropical species of Myopa are known, three from Mexico and one from Chile. In this study we describe two new species: Myopa nebulosa sp. nov. distributed from northern Chile to the Maule region of central Chile, and Myopa bozinovici sp. nov. from Mediterranean ecosystems of central Chile. We also re-describe the conspicuous species Myopa metallica Camras and provide an updated key to all Neotropical species of this genus. The natural history of these species is unknown. Myopa species are not abundant and their habitats may be threatened by land change use.